2023
DOI: 10.1093/europace/euad210
|View full text |Cite
|
Sign up to set email alerts
|

25 years of basic and translational science in EP Europace: novel insights into arrhythmia mechanisms and therapeutic strategies

Carol Ann Remme,
Jordi Heijman,
Ana M Gomez
et al.

Abstract: In the last 25 years, EP Europace has published more than 300 basic and translational science articles covering different arrhythmia types (ranging from atrial fibrillation to ventricular tachyarrhythmias), different diseases predisposing to arrhythmia formation (such as genetic arrhythmia disorders and heart failure), and different interventional and pharmacological anti-arrhythmic treatment strategies (ranging from pacing and defibrillation to different ablation approaches and novel drug-therapies). These st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Computer modelling and simulation have been widely used for testing optimal ablation therapies of AF 33 in virtual cohorts. Early work by Hwang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Computer modelling and simulation have been widely used for testing optimal ablation therapies of AF 33 in virtual cohorts. Early work by Hwang et al .…”
Section: Discussionmentioning
confidence: 99%
“…These can, in part, be addressed using patient-specific induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CMs), especially when combined with an isogenic cell line as control. However, given the limitations of these cell lines in studying various important features including the impact of aging and development of structural disease, 57 mouse models remain relevant for studying mechanisms underlying SCN5A -related cardiac dysfunction with the aim of identifying novel clinically relevant diagnostic, prognostic, and therapeutic tools. The current study also emphasizes the importance of using various mouse strains in such studies, as disease phenotype is strongly dependent on genetic background.…”
Section: Discussionmentioning
confidence: 99%
“… 10 This is even more important, considering that in the past decade no novel antiarrhythmic agent became available. 11 Sodium channel blocker remains underutilized, even in patients without structural heart disease, 12 , 13 most likely due to fear of proarrhythmia. 14 The Cardiac Arrhythmia Suppression Trial (CAST) observed proarrhythmic effects of flecainide and encainide in patients with prior myocardial infarction, frequent ventricular premature beats, and HF with reduced ejection fraction.…”
Section: Introductionmentioning
confidence: 99%